METODE LATIHAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP HASIL LATIHAN SHOOTING FREE THROW BOLA BASKET - Agung Mahendra (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2020)
The purpose of this study was to the increase in shooting free throw. The 2 x 2 factorial design experimental research method. Research result: 1) The difference in the effect of the training method distributed practice (mean 4,625) and massed practice (mean 6,875) towards results shooting free throw, Fcount 9,366 and significant rate 0,010 smaller than significant rate 0,05. 2) The differences in the effect of high flexibility of the wrist (mean 6,75) and low (mean 4,75), Fcount 11,854 and significant rate 0,005 smaller than significant rate 0,05. 3) Interaction between training methods distributed practice (mean 4,75) and massed practice (mean 8,75) and high flexibility of the wrist (mean 5,0) and low (mean 4,5) towards results shooting free throw, Fcount 7,171 and significant rate 0,020 smaller than significant rate 0,05. Conclusion: 1) There is a difference in effect between the training methods distributed practice and massed practice on the results of shooting free throw basketball. 2) There are differences in influence between students with high and low wrist flexion. 3) There is an interaction between the training method and wrist flexion.Keyword : Distributed Practice Method, Massed Practice Method, Shooting Free Throw.